Nasopharyngeal Carcinoma in the Nias Tribe Indonesia: Prevalence, Risk Factors, and Characteristics - Hana Isal Salina Ginting; Mery Silvia Harahap (Archives of The Medicine and Case Reports, 2025)
Nasopharyngeal carcinoma (NPC) is a malignancy with a distinctive racial and geographical distribution, exhibiting a high prevalence in Southeast Asia, including Indonesia. The Nias tribe, an indigenous group in Indonesia, has a particularly high incidence of NPC, which may be linked to unique environmental and genetic factors. This study aimed to investigate the prevalence, risk factors, and characteristics of NPC among the Nias people to inform targeted prevention and control strategies. A retrospective study was conducted on 150 NPC patients treated at a referral hospital in Medan, Indonesia, between 2018 and 2023. Data were collected from medical records, including demographics, clinical presentation, Epstein-Barr virus (EBV) infection status, dietary habits, and environmental exposures. Descriptive statistics and comparative analyses were performed to identify risk factors associated with NPC in the Nias population. The prevalence of NPC among the Nias tribe was 30% (45 out of 150 NPC patients). The majority of Nias patients were male (60%) and aged 40-60 years (70%). EBV infection was prevalent in 80% of the Nias patients. Significant risk factors included consumption of preserved foods (78%), exposure to firewood smoke (65%), and a family history of NPC (20%). Most patients presented with advanced-stage disease (III and IV), with common symptoms such as neck lumps, epistaxis, and nasal obstruction. In conclusion, NPC poses a substantial health burden on the Nias tribe. EBV infection, consumption of preserved foods, exposure to firewood smoke, and genetic predisposition are significant risk factors. Public health interventions should prioritize early detection through EBV screening, health education on risk factors, and promotion of alternative cooking fuels to reduce exposure to carcinogens.